Euplotes nobilii Valbonesi and Luporini 1990 - Yeo, Jeong Hyeon; Jung, Pablo Quintela-Alonso and Jae-Ho (Zenodo, 2023)
2. Euplotes nobilii Valbonesi and Luporini, 1990 (Fig. 2) Material examined. Marine water (salinity 21‰) collected from Gyeonpo Lake, Jeo-dong, Gangneung-si, Gangwon-do, Korea (37°48′6″N, 128°54′14″E) on July 23, 2020. Diagnosis. Body size about 29.7-41.7 × 14.9-26.4 μm (on average 33.8 × 20.0 μm) after protargol impregnation, body shape sharp oval, left margin slightly more convex than right margin, 6 dorsal and 3 ventral ridges; one macronucleus C-shaped with one spherical micronucleus attached; 19-29 adoral membranelles; 10 frontoventral, 5 transverse, 2 caudal and 1 marginal cirrus; 7 or 8 dorsal kineties, of which the middle kinety composed of 6-9 dikinetids; dorsal argyrome pattern of double- patella type. Distribution. Probably cosmopolitan (Greenland, Tierra del Fuego, Terra Nova, Antarctic Ocean and Korea; Valbonesi and Luporini, 1990a; Di Giuseppe et al. , 2013). Remarks. The Korean population corresponds well with the type population (Valbonesi and Luporini, 1990a), although one outlier specimen from the Korean population showed a slightly higher number of adoral membranelles (i.e., 29 adoral membranelles) than the type population (19-23 vs. 18-22). Compared to other species in the genus, E. rariseta Curds et al. , 1974 highly resembles E. nobilii , but it differs from the latter by the number of dikinetids in the middle kinety (maximum 6 vs. 6-9) (Curds et al. , 1974; Valbonesi and Luporini, 1990a). However, the description of the morphometric features of the dorsal kinety of E. rariseta has experienced some variation since it was originally described, to include variability among populations, i.e., (number of dorsal kineties/number of dikinetids on mid-kinety) 5/maximum 6 (Wilbert and Kahan, 1981), 6/5-7 (Kim and Lee, 2019), 7/7 (Dallai et al. , 1987), 7/5-7 (Song and Packroff, 1997; Ma et al. , 2007), 7/8-10 (Valbonesi and Luporini, 1990a). The Antarctic population reported by Valbonesi and Luporini (1990a) might be new to science, as already mentioned by the authors, because it has more adoral ...